2021
DOI: 10.1007/s40843-021-1749-5
|View full text |Cite
|
Sign up to set email alerts
|

Bimetallic phthalocyanine heterostructure used for highly selective electrocatalytic CO2 reduction

Abstract: Heterogeneous molecular catalysts, such as metal phthalocyanines, are efficient electrocatalysts for CO 2 reduction reaction (CO 2 RR). However, the rational design and synthesis of a molecular catalyst-based heterostructure for CO 2 RR remains challenging. Herein, we developed a crystalline bimetallic phthalocyanine heterostructure electrocatalyst (CoPc/FePc HS), which achieved an excellent CO 2 -to-CO conversion efficiency (99%) and outstanding long-term stability after 10 h of electrocatalysis. Density func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(13 citation statements)
references
References 65 publications
0
13
0
Order By: Relevance
“…11−17 However, as most of the obtained SACs have M (center metal)−N coordination, the tunability of the central metal atom electronic state is limited by pure N coordination. 18 Yu et al reported a Sn SAC named SnN 3 O 1 with three N atoms and one O atom coordinated with Sn in the first coordination shell. 19 This catalyst not only exhibited an excellent Faradaic efficiency of CO as high as 94% at −0.7 V vs RHE but also showed an outstanding turnover frequency (TOF) of up to 23340.5 h −1 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…11−17 However, as most of the obtained SACs have M (center metal)−N coordination, the tunability of the central metal atom electronic state is limited by pure N coordination. 18 Yu et al reported a Sn SAC named SnN 3 O 1 with three N atoms and one O atom coordinated with Sn in the first coordination shell. 19 This catalyst not only exhibited an excellent Faradaic efficiency of CO as high as 94% at −0.7 V vs RHE but also showed an outstanding turnover frequency (TOF) of up to 23340.5 h −1 .…”
mentioning
confidence: 99%
“…Recently, 3d carbon-supported transition-metal single-atom catalysts (SACs) have been extensively explored for the ECRR. However, as most of the obtained SACs have M (center metal)–N coordination, the tunability of the central metal atom electronic state is limited by pure N coordination . Yu et al reported a Sn SAC named SnN 3 O 1 with three N atoms and one O atom coordinated with Sn in the first coordination shell .…”
mentioning
confidence: 99%
“…The continuously excessive release of greenhouse gas, CO 2 , has caused serious global climate warming and environmental degradation. In this regard, the emerging sequestration [1], chemical fixation [2], and electro/photo/thermochemical reduction technologies [3][4][5][6][7][8][9] have been developed to alleviate CO 2 emissions. The electrochemical CO 2 reduction reaction (CO 2 RR) to yield high-value-added fuels and chemicals provides a promising approach towards an sustainable carbon-cycle utilization, especially when powered by renewable energy resources [10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, as a greenhouse gas, excess CO 2 emission results in a severe increase in the global ambient temperature [2][3][4][5]. The renewable energy-driven electrochemical reduction of CO 2 to high-valueadded chemicals, such as CO [6][7][8][9], HCOOH [10,11], CH 4 [12], CH 3 OH [13], and C 2 products [14,15], has been considered an environmentally viable and economic strategy for alleviating the abovementioned issues [16][17][18]. As evaluated from the technoeconomic prospect, formic acid presently has the highest net value, and it is easy to store and transport as a liquid product [19].…”
Section: Introductionmentioning
confidence: 99%